Exploring perceived cognitive load in learning programming via Scratch - Ünal Çakiroğlu; S. Sude Suiçmez; Yılmaz B. Kurtoğlu; Ayhan Sari; Suheda Yildiz; Mücahit Öztürk (Association for Learning Technology, 2018)
The purpose of this study is to investigate the perceived cognitive load and its effects on the academic performance in Scratch-based programming. The four main concepts of programming (sequences, operators, conditions and loop) were delivered in the instructional package. Participants were 12 sixth-grade students enrolled at a public secondary school. The results from quantitative and qualitative instruments indicated that students' perceived cognitive loads were close to each other among four programming concepts. The attractive interface of Scratch was somewhat useful but some parts of the interface were problematic for achieving the programming tasks. This study concludes with suggestions for Scratch practitioners and researchers to pay attention to the sources of cognitive load effects.